Venous malformation as source of a tarsal tunnel syndrome: treat the source or the cause of the complaints? A case report*. Issue 3 (4th May 2018) - Mufty, H.; Matricali, G. A.; Thomis, S.
Abstract: Painful tarsal tunnel syndrome is a compression neuropathy with a variety of possible sources. As it presents a challenging differential diagnostic problem, it is often under-diagnosed. Among the intrinsic and extrinsic factors, varicose veins are the main source in case of a venous etiology. We report a case of a 39-year old male patient who presented with complaints of paresthesia and excessive pain of the right foot, especially the medial side. Further work up by ultrasonography, magnetic resonance imaging and electromyography revealed an extensive congenital venous malformation of the right lower limb with subsequent compression of the tibial nerve in the tarsal tunnel. We did not treat the source, but the cause by open tarsal tunnel release. Excellent result with immediate full relieve of the patients complaints was achieved.